2010
DOI: 10.1128/jcm.02098-09
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Susceptibility to Teicoplanin and Vancomycin in Coagulase-Negative Staphylococci Isolated from Orthopedic-Device-Associated Infections

Abstract: We studied 315 coagulase-negative Staphylococcus strains recovered prospectively during 240 surgical procedures (206 subjects) from proven or suspected device-associated bone and joint infections. Sixteen strains (5.1%) had decreased susceptibility to glycopeptides: 15 (12 S. epidermidis strains, 2 S. capitis strains, and 1 S. haemolyticus strain) to teicoplanin alone (MIC of 16 mg/liter, n ‫؍‬ 9; MIC of 32 mg/liter, n ‫؍‬ 6) and one (S. epidermidis) to both teicoplanin and vancomycin (MIC, 16 and 8 mg/liter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
3
38
2
3
Order By: Relevance
“…8,11,12 Other species which have been reported to be glycopeptide non-susceptible include S. lugdunensis, S. capitis and S. simulans. 2,4,6,13 However, none of these species were identified as Teico-NS in the current study. CoNS from patients in ICU were more likely to be Teico-NS.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…8,11,12 Other species which have been reported to be glycopeptide non-susceptible include S. lugdunensis, S. capitis and S. simulans. 2,4,6,13 However, none of these species were identified as Teico-NS in the current study. CoNS from patients in ICU were more likely to be Teico-NS.…”
Section: Discussionmentioning
confidence: 51%
“…8 Other studies have reported reduced susceptibility overall to glycopeptides at 5.1% and teicoplanin at 8.1%. 2 Similarly, our study showed 7.2% of isolates to be Teico-NS with vancomycin resistance at 0.3%.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…7 Both MRSA and MRSE strains are also usually resistant to other antibiotics, and although vancomycin remains the elective therapy for these cases, its efficacy has been declining over the last few years. 8,9 For this reason, other antibiotics have recently been considered as alternatives to vancomycin. [10][11][12][13][14][15] Despite these facts, antimicrobial susceptibility remains extremely variable among these microorganisms, making it necessary to perform individual susceptibility studies for each strain to select the best antibiotic combination for treatment.…”
Section: Introductionmentioning
confidence: 99%